Prevención de enfermedades ocupacionales en el área Odontológica Distrito Chambo Riobamba, 2019 - Chamba Agila, Gabriela del Cisne (2023)
ABSTRACT: The main objective of this study was to determine the most frequent occupational diseases that occur in dentists of the Chambo Riobamba District 2019, in order to establish what are the alterations that occur in work activity, due to stress, exhaustion or by the positions that are adopted daily in their work, among other factors usually exposed, for its execution an interview with a questionnaire of questions was applied as a technique, for which the research is constituted as field, descriptive, observational, and cross-sectional, 53 professionals from the dental area were surveyed, then this information was processed and analyzed using the statistical program SPSS v.27. The results indicated that the most frequent occupational diseases were those that correspond to the psychosocial risk classification with 64%, of which are emotional irritability, followed by ergonomic risks with 62% carpal tunnel syndrome, and the risks chemicals with 58% hypersensitivity to latex, these data are also related to the organization, time and work breaks, excessive and repetitive use of vibratory instruments, forced position of the hand, handling of chemical and biological materials and the level of of application of prevention protocols for the management of work equipment and tools. Finally, a guide on the prevention of occupational risks and diseases is proposed with the purpose of informing about the risks at the work level and their possible consequences in the future. Keywords: Occupational health, occupational disorders, risk factors in dentists, occupational risk prevention.